Impact of Scaffolding Learning Strategy on Pre-Service Teachers’ Attitude to Cybercrime Prevention (British Journal of Multidisciplinary and Advanced Studies, 2023)
The study investigated the impact of scaffolding learning strategy on pre-service teachers’ attitude to cybercrime prevention. The study adopted the quasi-experimental research design of the survey type. The following instrument was developed by the researcher and used for the study, namely: Scaffolding Learning Strategy Guide and Lecture Note (SLSG), Conventional Method Guide and Lecture Note (CMG), Attitude to Cybercrime Prevention Scale (ACPS) and Computer Literacy Test (CLT). The participants for this study were selected using multistage sampling procedure. The first stage involved the use of simple random sampling technique to select three universities (one university for each learning strategy) in the region i.e. Southwest, Nigeria. This was followed by the use of purposive sampling technique to select the department of Social Studies education in each of the universities was selected. Consequently, intact class in each of the selected universities was used alongside three research assistants and three lecturers of the department. The data obtained through the administration of the instruments was analysed using descriptive and inferential statistics. All the hypotheses were tested and decisions were taken at 0.05 level of significance. The findings of the study revealed that Scaffolding Learning Strategy (SLS) has no effect on the attitude of Social Studies Pre-service Teachers’ attitude to cybercrime prevention, teachers’ gender does not affect their attitude towards cybercrime prevention and computer literacy does not influence the attitude of social studies pre-service teachers to cybercrime prevention. Therefore, it was recommended that the use of instructional strategies should be well articulated so as to bring about change in the attitude of the learners, gender of the learners should not be seen as factor affecting the attitude of learners towards learning. Hence, during teaching, teachers should give room for gender disparity among the learners and emphasis should be place on the computer literacy of learners. That is, learners should be encouraged to have knowledge of the use of computers in teaching and learning process.